Global trends in perioperative stroke research from 2003 to 2022: a web of science-based bibliometric and visual analysis - Ji, Shunpan; Shi, Yue; Fan, Xiaojing; Jiang, Tian; Yang, Xiaoming; Tao, Tianzhu; Ye, Bo (Frontiers in Neurology, 2023)
Background Perioperative stroke is a potentially devastating complication in surgical patients, which has attracted global attention. This retrospective bibliometric and visual analysis evaluates the status and global trends in perioperative stroke research. Methods Papers published between 2003 and 2022 were retrieved from the Web of Science core collection. Extracted data were summarized and analyzed using Microsoft Excel and further bibliometric and co-occurrence analyses were conducted using VOSviewer and CiteSpace software. Results Publications on perioperative stroke have increased over the years. The USA topped the list of countries with the highest number of publications and citations, while Canada had the highest mean citation frequency. The Journal of Vascular Surgery and Annals of Thoracic Surgery had the highest number of publications and citation frequency for perioperative stroke. Regarding authors, Malas, Mahmoud B. contributed the most publications to the field, and Harvard University had the highest number of publications (409 papers). Based on an overlay visualization map, timeline view, and the strongest strength burst of keywords, “antiplatelet therapy,” “antithrombotic therapy,” “carotid revascularization,” “bleeding complications,” “postoperative cognitive dysfunction,” “intraoperative hypotension,” “thrombectomy,” “cerebral revascularization,” “valve surgery,” “tranexamic acid,” and “frozen elephant trunk” were trending topics in perioperative stroke research. Conclusion Publications regarding perioperative stroke have experienced rapid growth in the past 20 years and are likely to continuously increase. Research on perioperative antiplatelet and antithrombotic, cardiovascular surgery, postoperative cognitive dysfunction, thrombectomy, tranexamic acid, and frozen elephant trunk has attracted increasing attention, and these topics are emerging hotspots of present research and possible candidates for future research.